2019
DOI: 10.1126/science.aat8051
|View full text |Cite
|
Sign up to set email alerts
|

Tunable intrinsic strain in two-dimensional transition metal electrocatalysts

Abstract: Tuning surface strain is a powerful strategy for tailoring the reactivity of metal catalysts. Traditionally, surface strain is imposed by external stress from a heterogeneous substrate, but the effect is often obscured by interfacial reconstructions and nanocatalyst geometries. Here, we report on a strategy to resolve these problems by exploiting intrinsic surface stresses in two-dimensional transition metal nanosheets. Density functional theory calculations indicate that attractive interactions between surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
356
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 438 publications
(391 citation statements)
references
References 64 publications
6
356
2
Order By: Relevance
“…The size of the particles will further influence the strain exerted across the particle, which may further affect the d electronic states. This strain effect is well‐discussed in literature for alloy films . Despite the quantitative differences, the relative accuracy of the predicted shifts replicates the correct trend in electron energies, even for compositional changes of the same alloying metal.…”
Section: Resultssupporting
confidence: 74%
“…The size of the particles will further influence the strain exerted across the particle, which may further affect the d electronic states. This strain effect is well‐discussed in literature for alloy films . Despite the quantitative differences, the relative accuracy of the predicted shifts replicates the correct trend in electron energies, even for compositional changes of the same alloying metal.…”
Section: Resultssupporting
confidence: 74%
“…As is well known, the ultrathin structure in metallic nanocrystals facilitates the generation of compressive strain, which could effectively tune the electronic structure of metal for the optimized catalytic property . Impressively, the Pt–Cu–Mn UNFs possess ultrathin structure as compared to Pt–Cu–Mn PNFs.…”
Section: Resultsmentioning
confidence: 99%
“…In recent studies, tuning surface strain has become one of the most powerful strategy to boost the electrocatalytic properties of Pt‐based catalysts . It could modulate the surface electronic structure to an appropriate condition for energetics of reaction intermediates, resulting in the enhancement of catalytic performance . Previous reports have demonstrated that tuning the surface strain of Pt‐based catalysts could dramatically improve the catalytic activity for ORR due to the optimal oxygen adsorption energy and 1% compressive strain could increase the catalytic activity of Pt catalyst by more than 300% .…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Particularly,t he advance in alkaline membrane technologies has stimulated intensive studies on HzOR to be used in practical HzFCs. [4] In this context, enormous efforts have been devoted towards developing efficient, low-cost anode electrocatalysts for HzOR to replace the costly state-of-the-art platinum (Pt) based nanomaterials, [5][6][7] along with optimizing the electrode fabrication craft. [8,9] Recently,s ingle-atom catalysts,e specially atomically dispersed metals anchored on conductive nitrogen (N)-doped carbons (AMCs), have been intensively studied for numerous applications [10][11][12][13][14][15] because of their maximized atom utilization, unusual electronic structure and intriguing properties that differ from their nanoparticles (NPs) counterpart in terms of that is,improved activity and/or selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…c) CV curves of SeNCM-1000 in 1 m KOH with 100 mm N 2 H 4 at different scan rates(5,10,15,20,40,100 mVs À1 ). b) CV curves of SeNCM-x,S epowder and NCM-1000 for HzOR (100 mm N 2 H 4 ,1m KOH, scan rate 5mVs À1 ).…”
mentioning
confidence: 99%